2019
DOI: 10.2196/13023
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Volunteer Family Connect Program in Reducing Isolation of Vulnerable Families and Supporting Their Parenting: Randomized Controlled Trial With Intention-To-Treat Analysis of Primary Outcome Variables

Abstract: BackgroundVolunteer home visiting is a widely adopted community-based approach to support families by linking isolated or vulnerable families with community volunteers who visit their homes weekly over approximately 12 months. This study seeks to robustly evaluate the effectiveness of this model of support for families with young children.ObjectiveThis paper reports the intention-to-treat analysis of primary and secondary outcomes for a pragmatic randomized controlled trial (RCT) of the Volunteer Family Connec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 22 publications
(28 reference statements)
0
12
0
1
Order By: Relevance
“…Social support is a well-established protective factor for mother-hild health in Latinas (Luecken et al, 2013), which may mitigate psychosocial stress by counteracting the social exclusion underlying both discrimination and acculturative stress. Although brief nurse-led psycho-education programs may mitigate postpartum depressive symptoms in the general population (Fisher et al, 2010), vulnerable families may benefit from interventions that explicitly integrate social support, such as community-based volunteer home visiting (Grace et al, 2019). In fact, the company of other women with similar experiences may create a sense of community and belonging (Small et al, 2011).…”
Section: Clinical and Research Implicationsmentioning
confidence: 99%
“…Social support is a well-established protective factor for mother-hild health in Latinas (Luecken et al, 2013), which may mitigate psychosocial stress by counteracting the social exclusion underlying both discrimination and acculturative stress. Although brief nurse-led psycho-education programs may mitigate postpartum depressive symptoms in the general population (Fisher et al, 2010), vulnerable families may benefit from interventions that explicitly integrate social support, such as community-based volunteer home visiting (Grace et al, 2019). In fact, the company of other women with similar experiences may create a sense of community and belonging (Small et al, 2011).…”
Section: Clinical and Research Implicationsmentioning
confidence: 99%
“…Higher levels of SC have been associated with decreased caregiver stress in families with children aged 7 to 11 years 11 and increased caregiver's sense of confidence and involvement with young children aged 0 to 5 years. 12,13 Social support demonstrated a positive association with child behavioral outcomes. 14,15 Research shows that lower SC of families may increase the risk for child abuse.…”
Section: Introductionmentioning
confidence: 96%
“…An integrative literature review reported that volunteer social support (or mentorship) programs can improve maternal mental health, parenting skills, parent-child relationships, and social capital (14). There are few evidence-based mentorship programs to support mothers between pregnancy and early parenthood, and most focus on vulnerable populations (e.g., 15,16). Mitchell et al (16), in a qualitative study of Mentoring Mums, a program that bridged the gap between mothers and professional support, conceptualized the role of volunteer mentors as "befriending" (p. 40) and building a network of connections for young mothers at risk for poor parenting.…”
Section: Introductionmentioning
confidence: 99%
“…Mitchell et al (16), in a qualitative study of Mentoring Mums, a program that bridged the gap between mothers and professional support, conceptualized the role of volunteer mentors as "befriending" (p. 40) and building a network of connections for young mothers at risk for poor parenting. Grace et al (15), in their seven-site randomized controlled trial of the Volunteer Family Mentor program for vulnerable and isolated families, reported a group difference in parenting sense of competence favoring the intervention group, but no group differences on maternal mental health. In a systematic review of the effects of support from the infant's grandparents, Riem et al (17) found that support from maternal grandmothers constituted a protective factor against the development of postnatal mental health problems in the mother.…”
Section: Introductionmentioning
confidence: 99%